A Critique Towards Australian Work and Holiday Visa Subclass 462: Where Does It Leave Indonesian Citizen? - Dewi, Yetty Komalasari; Setiawati, Wenny, wsetiawati@gmail.com (UI Scholars Hub, 2020)
Work and Holiday Visa (WHV) is one of the product outcomes from the agreement that Australia engaged with state partners. Initially, this visa aims for cultural exchange and then shifted to supply the needs of Australian industry. In essence, this visa granted the holder one year to spend time in Australia consisting of six months for working and six months for travelling. However, in its application, there are mistreatments on the WHV holder, and there is no sufficient labour protection towards the worker. This paper examines the position of WHV holder in Australia, protection for the worker, and the view of the Indonesian Government on the WHV. It also discusses the Indonesia – Australia Comprehensive Economic Partnership Agreement (IA-CEPA) on the WHV context since there is a provision regarding WHV in the agreement. The paper concludes that the WHV is not a mere cultural exchange program, but a type of labour migration. The fact that Government of Indonesia still considered WHV as a cultural program is not enough for the safety of Indonesian citizens which partakes the program, it should be governed by the labour law and provided by sufficient protection. The Government of Indonesia failed to see this as part of their scope of protection in IA-CEPA, and the Australian Government also did not set a clear context on WHV. Therefore, the GOI should shift its view on the WHV and take necessary measures to provide better labour protections under this scheme.